Numerical Simulation of Two-phase Separation in T-junction - Huei Ming, Low (Universiti Teknologi Petronas, 2013)
T-junctions are commonly used in distributing two-phase flow by piping networks especially in oil and gas industries. However, the nature splitting of liquid-gas phases is a major challenge and is complicated due to the large number of variables that influence it. Understanding the behavior of two-phase flow through a T-junction is very essential as it has significant impact on oil and gas transportation pipeline networks, operation and control of process and power industries and lastly the maintenance efficiency of all the components downstream from the junction. This paper provides a detailed analysis on the effect of associated variables on phase separation efficiency in T-junction. Hence, the analysis uses and develops a numerical model for simulation of two-phase flow distribution in T-junction to elucidate an in depth understanding on two-phase separation at different operating conditions and parameters. In order to achieve the objective, the developed model consists of horizontal main arm and vertical side arm while CFD method is employed to simulate the fluid flow. The present study identifies that the overall mass split ratio, the initial gas saturation and gas density are the most influential factors on fraction of gas taken off in T-junction. Subsequently, the effect of inclination angle of gravity on flow split is investigated and it does not play a significant role on phase separation. At the end of this project, the phenomenon of phase maldistribution when a two-phase mixture passes through a T-junctions is well understood and hence the underlying potential as a simple, cost saving, passive partial separator is able to be included in the design of pipeline networks in the petroleum industry.